Identification of mechanisms conferring an enhanced immune response in mice induced by CVC1302-adjuvanted killed serotype O foot-and-mouth virus vaccine. Issue 43 (8th October 2019) - Du, Luping; Yu, Xiaoming; Hou, Liting; Zhang, Dong; Zhang, Yuanpeng; Qiao, Xuwen; Hou, Jibo; Chen, Jin; Zheng, Qisheng
Abstract: The adjuvant CVC1302 was previously shown to efficiently enhance the immunogenicity of killed foot-and-mouth disease virus (FMDV) in mice and piglets. However, the underlining mechanism of action of CVC1302 remains unclear, especially at local injection sites and draining lymph nodes. Since the FMDV vaccine is administrated intramuscularly in field settings, we studied local immune responses to FMDV following intramuscular injection in mice, and found that CVC1302-adjuvanted killed FMDV (KV-CVC1302) induced secretion of several chemokines in murine muscle tissues, including MCP-1, MIP-1α, and MIP-1β. The number of monocytes recruited to the site of injection was significantly higher in mice immunized with KV-CVC1302 compared with mice immunized with killed FMDV alone (KV). iTAQ-based quantitative proteomic assays were additionally employed to explore the molecular mechanisms of CVC1302 action in the draining lymph nodes. A total of 35 proteins were identified as being differentially expressed among the control group, KV-immunized group and KV-CVC1302-immunized group at 10 days post immunization (dpi). Proteins exhibiting differential expression were mainly involved in signal transduction, apoptosis, endocytosis and innate immune responses. Pathway analysis demonstrated that AMPK, phospholipase D, cAMP, Rap1, and MAPK signaling pathways were potentially induced by the immunopotentiator CVC1302. Understanding the local mechanism of CVC1302 action at injection sites and draining lymph nodes will provide new insights into the development of FMDV vaccines.